Pengaruh Pembiayaan Mudharabah Dan Murabahah Terhadap Profitabilitas BTM Al-Kautsar Kota Makassar 2016-2022 - Andi Ulfa Ardiah Ramadhani Faisal Ulfa; Agusdiwana Suarni; Muhammad Khaedar Sahib (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2024)
Abstract— The purpose of this study was to determine theeffect of Mudharabah and Murabahah Financing on theProfitability of Baitut Tamwil Muhammadiyah Al-Kautsar. This study uses secondary data, which originates from thefinancial reports on mudharabah and murabahah financing published by BTM Al- Kautsar. This study uses statisticalanalysis, namely data analysis that takes into account therelationship between the dependent variable (mudharabahand murabahah) and the independent variable (profitability)with time series data in the 2016-2022 analysis period. The results of the mudharabah financing study did not have asignificant effect on profitability at BTM Al-Kautsar 2016-2022 as evidenced by the obtained t table of 2,776. Because t count is smaller t table (0.818 < 2.015). then Ho's decision is accepted and Ha is rejected. Murabahah financing has no significant effect on profitability at BTM Al-Kautsar 2016-2022 as evidenced by the obtained t table of 2,015. Becausethe t count is smaller than the table (-0.943 < 2,015). then Ho's decision is accepted and Ha is rejected.